Efficacy and safety of PARP inhibitor maintenance therapy for ovarian cancer: a meta-analysis and trial sequential analysis of randomized controlled trials - Guojuan Sun; Yi Liu (Frontiers Media S.A., 2024)
BackgroundThe landscape of poly (ADP-ribose) polymerase (PARP) inhibitor treatment for ovarian cancer (OC) is continually evolving. This research aimed to evaluate the efficacy and safety of PARP inhibitors compared to placebo as a maintenance therapy for OC patients.MethodsWe conducted a search of PubMed, Embase, Web of Science, and the Cochrane Library databases for randomized controlled trials (RCTs) involving the use of PARP inhibitors as maintenance therapy in OC patients, up to 16 June 2024. Data regarding progression-free survival (PFS), overall survival (OS), chemotherapy-free interval (CFI), time to first subsequent therapy or death (TFST), time to second subsequent therapy or death (TSST), and treatment-emergent adverse events (TEAEs) were aggregated. Pooled hazard ratio (HR) and their corresponding 95% confidence intervals (CI) were calculated for PFS, OS, CFI, TFST, and TSST. Additionally, the relative risk (RR) and 95% CI for TEAEs were determined.ResultsThis meta-analysis encompassed 20 RCTs involving 7,832 participants. The overall analysis demonstrated that maintenance therapy with PARP inhibitors led to significant improvements in PFS (HR: 0.398, 95% CI = 0.339-0.467, 95% PI = 0.219-0.724), OS (HR: 0.677, 95% CI = 0.582-0.788, 95% PI = 0.546-0.839), CFI (HR: 0.417, 95% CI = 0.368-0.472, 95% PI = 0.265-0.627), TFST (HR: 0.441, 95% CI = 0.391-0.498, 95% PI = 0.308-0.632), and TSST (HR: 0.574, 95% CI = 0.507-0.649, 95% PI = 0.488-0.674) compared with placebo. Subgroup analyses further indicated that PARP inhibitor maintenance treatment significantly improved PFS, regardless of homologous recombination status (all p < 0.05). However, the risks of any grade (RR = 1.046, 95% CI = 1.032-1.059, 95% PI = 1.028-1.055) and grade ≥3 TEAEs (RR = 2.931, 95% CI = 2.641-3.253, 95% PI = 2.128-3.792) were increased by PARP inhibitor maintenance therapy compared to placebo.ConclusionOur research elucidated the benefits of maintenance therapy with PARP inhibitors in patients with OC, showing improvements in PFS, OS, CFI, TFST, and TSST. Vigilance regarding TEAEs is paramount for clinicians implementing PARP inhibitor maintenance therapy in clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024560286.